The Relationship Between Academic Burnout And Anxiety Levels Among Students Studying From Home In The Nursing Study Program At The Abdi Nusantara Health College In 2025 - Futriani, Elfira Sri; Saogo, Lasma Angelita; Wijayanti, Puji (Jurnal Ners, 2026)
Background: Academic burnout is a condition where a person is emotionally tired, tends to depersonalize, and feels low personal achievement in students due to stress, lecture load or other psychological factors originating from the learning process. This condition reflects three main dimensions, namely emotional exhaustion, cynicism, and decreased personal efficacy, which can have a significant impact on students' academic performance and psychological well-being. Anxiety in students is a natural response to challenging situations, but tends to increase in college environments due to academic and social pressure. The American College Health Association survey shows that 25.9%–31.9% of students experience anxiety and stress. Academic burnout in overseas students causes students not to be optimal in completing academic assignments, the emergence of feelings of laziness, procrastination of assignments, depression, and uncertainty about graduation, including unstable financial and social factors. Research Objective: To determine the relationship between academic burnout and anxiety levels in migrant students at STIKes Abdi Nusantara nursing study program in 202. Research Method This research uses quantitative methods with an analytical observational approach. The research design used is correlational with a cross-sectional approach, where measurements of the independent variable and dependent variable are carried out simultaneously during one observation period. The target population in this study was 59 respondents. Research Results The research results show that the Chi-Square statistical test obtained a value of p.0.001 (p.value < 0.05), so based on the results above it can be interpreted that there is a relationship between academic burnout and the level of anxiety in migrant students at STIKes Abdi Nusantara Nursing Study Program in 2025. Conclusions and Suggestions: There is a significant relationship between academic burnout and the level of anxiety in migrant students of the STIKes Abdi Nusantara Nursing Study Program in 2025. Migrant students are expected to be able to improve their ability to manage academic stress through effective time management, setting learning priorities, and implementing adaptive coping strategies. Considering that the first 3–6 months of the overseas phase is a relatively vulnerable period, students need to be more active in building social support, both with peers and supervisors. Apart from that, maintaining a balance between academic activities and rest time is an important step to prevent an increase in academic burnout and anxiety.